Bibliometric and visual analysis in the field of traditional Chinese medicine in cancer from 2002 to 2022 - Bai, Facheng; Huang, Zhenguang; Luo, Jun; Qiu, Yue; Huang, Shuwen; Huang, Chenglong; Liu, Taotao; Zhang, Hongliang; Wang, Dandan (Frontiers in Pharmacology, 2023)
Objective: Traditional Chinese medicine (TCM) has been used as a complementary treatment for cancer patients, but there has been no quantitative comprehensive analysis of TCM's efficacy. The purpose of this paper is to explore the current status and hotspots of TCM in cancer research from 2002 to 2022, and provide a reference for future research.: We retrieved articles published between 2002 and 2022 from the Web of Science database and analyzed them using R software, VOSviewer, and Citespace software. Results: A total of 7,129 articles were included in this study. The publication rate of TCM cancer research increased steadily from 2002 to 2022, with a rapid increase from 2010 to 2021. China was the country with the most published articles, followed by the United States, Korea, Germany, and Japan. China was also the country with the most international collaborations, and China Medicine University and Shanghai University of Traditional Chinese medicine were the most representative cooperation centers. The Journal of Ethnopharmacology was the most published and cited journal. Apoptosis, expression, in-vitro, activation, and other related keywords were commonly used in these articles. Breast cancer, colorectal cancer, gastric cancer, liver cancer, and lung cancer were the most studied cancer types in TCM research. Pathway-related apoptosis, anti-inflammation, and oxidative stress were the hotspots and trends of TCM's anticancer mechanism. The metabonomic combined with network pharmacology was the main research method.Traditional Chinese medicine as an anti-cancer drug has received increasing attention from researchers worldwide, and it is expected to be a hotspot for developing new anti-cancer drugs in the future. Our study provides a comprehensive analysis of the current status and hotspots of TCM cancer research, which could serve as a valuable reference for future studies.